1999
DOI: 10.1038/sj.bjc.6690699
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the pancreas-specific gene in the peripheral blood of patients with pancreatic carcinoma

Abstract: SummaryThe prognosis of patients with pancreatic carcinoma remains very poor. To improve the therapeutic results, the early detection of this cancer is needed. The present study was performed to detect the pancreas-specific gene, chymotrypsinogen, in the peripheral blood from patients with pancreatic carcinoma by using reverse transcription polymerase chain reaction (RT-PCR) in order to evaluate the clinical significance of this gene. Ten patients with pancreatic carcinoma, two with acute pancreatitis, three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The monitoring of K-ras 12 somatic mutation ratio values in DNA fractions derived from tissue biopsy and the CFPB could have potential utility in observations related to the metastatic process known as micrometastasis (Tada et al 1993;Kuroki et al 1999;Koike et al 2002;Mataki et al 2004). This possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of K-ras 12 somatic mutation ratio values in DNA fractions derived from tissue biopsy and the CFPB could have potential utility in observations related to the metastatic process known as micrometastasis (Tada et al 1993;Kuroki et al 1999;Koike et al 2002;Mataki et al 2004). This possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CTRB mRNA was detected in some of PC cell lines (SW1990 and PaTu8988). In a previous study, it was shown that mRNA of CTRB gene could be detected in the peripheral blood of patients with pancreatic carcinoma as a genetic diagnostic marker (26). Further studies are needed to determine if the CTRB is a useful biomarker for PC.…”
Section: Discussionmentioning
confidence: 99%
“…Arrows indicate transcription merase chain reaction technique to be a useful diagnostic tool for pancreatic cancer. 53,54 Methylation-specific polymerase chain reaction is also an extremely sensitive assay which has the ability to detect a small number of circulating cancer cells in the peripheral blood. In fact, several studies have shown promoter hypermethylation in serum DNA in multiple tumor types to be a useful screening method for making an accurate diagnosis.…”
Section: Hypermethylation As a Diagnostic Markermentioning
confidence: 99%